Safety, Efficacy, and Predictive Factors of Conventional Epithelium-Off Corneal Crosslinking in the Treatment of Progressive Keratoconus. (31st May 2020) - Farhat, Rebecca; Ghannam, Mohamad Khaled; Azar, Georges; Nehme, Joseph; Sahyoun, Marwan; Hanna, Najib Georges; Abi Karam, Mariana; El Haber, Charbel; Schakal, Alexandre; Jalkh, Alexandre; Samaha, Ameed
Abstract : Purpose . To report predictive factors of outcome of conventional epithelium-off corneal crosslinking (CXL) in the treatment of progressive keratoconus. Methods . This is a monocentric observational retrospective study conducted at Eye and Ear International Hospital, Lebanon. All patients with progressive keratoconus who underwent CXL between January 2008 and January 2016, with minimal 3-years follow-up were included. Primary treatment outcomes were maximum keratometry (K max), best-corrected distance visual acuity (CDVA), and failure. Failure was defined as an increase of 1.00 diopters (D) or more in K max and/or an increase of 0.1 logMAR or more in CDVA and conversion to corneal transplantation. Statistical analysis was done to identify predictors of treatment success. Univariate and multivariate analyses were performed to determine the correlations between baseline parameters and outcomes, and an equation for predicting K max and CDVA was created. Results . 156 eyes of 102 patients were enrolled. The mean age was 23.85 ± 6.52 years. Failure occurred in 31 eyes (19.87%). Gender and thinnest pachymetry did not have any impact on postoperative outcomes. Concerning the CDVA outcome, multivariate analysis showed that a better preoperative CDVA was associated with higher improvement in CDVA, and higher baseline K max and higher posterior mean K were associated with a worse outcome CDVA. Regarding postoperative K max, a higher baseline K max, a worse baseline CDVA, and a younger age were associated with less flattening postoperatively. Conclusion . CXL is a safe and effective method in treating progressive keratoconus. However, the clinical benefits can differ among patients, and in our series, a nonnegligible number of cases show a continued progression of their ectasia. Further studies to identify predictors of postoperative progression prior to the procedure could help sort out good responders to treatment.